2016
DOI: 10.13189/ujm.2016.040704
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Motivation of Students at Sports Science Faculty as Football Sports Fans

Abstract: The aim of this study is to analyze motivation of students at sports science faculty as football sports fans.To collect data about motivation of students for the current research, "Sport Fans Questionnaire" was used which was developed by Karaoğlu and Tiryaki [1] and it was administered to a total of 273 students consisting of 179 male and 94 female students. For data analysis, SPSS statistical packet program was used for frequency analysis, descriptive statistic, independent t-tests and one-way ANOVA. Tukey t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Results of the analysis for the departments of the participants indicated that there was a significant difference in the departments of physical education and sports teaching and sports coaching. Belli et al, (2016) found a significant difference in favor of physical education and sports teaching department students in their study on sports sciences faculty students' football support. It can be said that the fans support their teams by buying tickets and licensed products to show their loyalty to their teams (Chiu et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Results of the analysis for the departments of the participants indicated that there was a significant difference in the departments of physical education and sports teaching and sports coaching. Belli et al, (2016) found a significant difference in favor of physical education and sports teaching department students in their study on sports sciences faculty students' football support. It can be said that the fans support their teams by buying tickets and licensed products to show their loyalty to their teams (Chiu et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Hirt et al [24] and Hoogland et al [25] also consider that strongly identified sports fans respond to the performance of the team as if team success were a personal success and the failure of the team were a personal failure. When considering Pereira [29] and Belli, Gürbüz and Biricik [30], for whom the most common reasons to be a football fan are the membership of the group, aesthetic, entertainment and eustress, it may be suggested that the dysfunctional behaviors of FCM can be related to motivation to relieve stress due to several factors beyond the football game. One of the most interesting results of this study concerns the fact that when comparing the normative values of the general population of the Portuguese version of the BSI with those of the FCM group, the latter presents significantly lower values for obsession-compulsion.…”
Section: Discussionmentioning
confidence: 99%
“…The former are more motivated by family reasons when compared to men. Fans seem to feel more motivated from the intrinsic point of view than from the extrinsic point of view [30].…”
Section: Predisposing and Predicting Factorsmentioning
confidence: 99%